Estudo do psiquismo de gestantes com diabetes melitus através do questionário para estilo de defesa (DSQ) e do questionário de morbidade psiquiátrica para adultos (QMPA) - Wutke, Érika Finotti (2009)
This study aimed at identifying, through Defense Style Questionnaire (DSQ), the ego defense mechanisms used by diabetic pregnant women and their association with the presence of mental disorders evaluated through the screening test QMPA (Psychiatric Morbidity Questionnaire for Adults). It is a sequential case-control study. Subjects were 100 pregnant women diagnosed with diabetes mellitus (gestational and pregestational diabetic women), who were being assisted by the Psychological Service offered in the Ambulatory Department and in the Infirmary for High Risk Pregnancy, and 100 clinically normal pregnant women who were being attended in the Ambulatory Prenatal Service Department, who formed the control group. Subjects were paired by age, educational level and the trimester of pregnancy. According to the results, the diabetic pregnant women tend to differ from the non-diabetic ones inasmuch as they use disadaptive defense mechanisms, such as: passive aggressiveness, projection, inhibition, somatization, fantasy, and refusing help. According to the QMPA scores, the group of diabetic pregnant women presented significant differences, when compared to the control group, concerning the following factors: anxiety/somatization, irritability/depression, and exaltation of humor. The values related to the group of diabetic pregnant women were higher than those related to the control group. The study suggests that diabetic pregnant women show more signs of regression than the non-diabetic ones. This conclusion may indicate the need for the implementation of a program for pregnant women devoted to the prevention of psychological disorders.